Hydrocarbons fuel upgradation in the presence of modified bi-functional catalyst. (10th October 2018) - Chawla, Muhammad; Rafiq, Sikander; Jamil, Farrukh; Usman, Muhammad Rashid; Khurram, Shahzad; Ghauri, Moinuddin; Muhammad, Nawshad; Al-Muhtaseb, Ala'a H.; Aslam, Muhammad
Abstract: Air pollutants such as NOX and SOX emitted from diesel combustion are one of the major concerns of the environment as well as human health. Aromatics in diesel fuel are one of the major sources of poor cetane number, which is tackled by selective ring opening of diesel to increase the cetane number. The present work's objective was at the ring opening of decalin over mono-functional and bi-functional catalysts. The catalyst, mordenite, is modified by treating with acid to increase its surface area for the better performance by aluminum leaching from its framework. The mordenite is used as support, and different metals like nickel and cobalt are impregnated. These catalysts were characterized, and the results indicate that the dealumination does not affect the structure and maintains its property as observed by X-ray diffraction (XRD) analysis. Brunauer–Emmett–Teller (BET) analysis shows that the surface area of catalyst increased from 342 to 366.3 m 2 /g due to extraction of aluminum. The morphology of catalysts was also maintained, and Si/Al ratio was increased due to dealumination of catalysts. The ring opening of decalin was examined by gas chromatograph mass spectroscopy (GC-MS) analysis, which indicates that ring opening of decalin with NiCo/dealuminated catalyst has higher conversion of 14.7% at 350 °C than other catalysts. Thus, modified catalyst can be a better source for providing high cetane hydrocarboneous fuels and membrane gas separation applications. Graphical abstract: Image 1 Highlights: Treatment of catalyst using acid leaching for better physiochemical properties. Synthesis of bi-functional catalysts for fuel upgradation. Catalysts evaluation by ring opening of decalin. Promising results based on analysis of liquid by GC-MS.